Analisis Spillover Effect Pertumbuhan Ekonomi antar Kabupaten/Kota di Kawasan Purwomanggung Jawa Tengah Tahun 1988-2018 - Maisi Hasna Mariyatul Qibti; R. Mulyo Hendarto (Universitas Diponegoro, 2020)
The empirical analysis of growth spillover effects is important because application of growth centers theories that has been done by developed countries and also developing countries still raise pro-cons. Regencies/cities in PURWOMANGGUNG Region have open characteristics, with almost the same economic structure. As a consequence of the openness, the economy in a region can be influenced by the behavior and dynamics of economic activity in the surrounding area. This study aims to identify the causal relationship inter-regional economic growth and analyze the spillover effects of economic growth between districts/cities in the PURWOMANGGUNG Region. The method used is the Granger Causality Test to identify the causal relationship inter-regional economic growth, and Vector Error Correction Model (VECM) to know the growth spillover effect between districts/cities in the PURWOMANGGUNG Region. The data used is GDRP at constant market prices in regencies/cities in the PURWOMANGGUNG Region within a period of 31 years from 1988 to 2018. The results show that the relationship of economic growth between regions is largely bidirectional. The spillover effect in each region has a spread effect and backwash effect. The spread effect in the development activities that has been done by each region in the PURWOMANGGUNG is greater than the backwash effect. This is consistent with Perroux hypothesized through the growth pole theories.